Human Hepatitis B Viral Proteins HBX and HBE: Roles in HepG2 Cell Line Survival and Cell Death - Holme, Andrea Lisa (2004)
Existing reports of viral hepatitis, resulting in liver cell death have not been fully explained with regards to the mechanism ofthe viral proteins involved. The objective of the study is to determine if any of the Hepatitis B viral proteins cause changes in the survival of human hepatocytes and if so by what means. The two main candidates for inducing survival changes were the precore proteins (HBE) and HBX, both of which have been reported to accumulate in the liver of patients and to trigger an immune response. The human liver HepG2 cell line was chosen to study the effect ,of these proteins during transient expression. The results from this study show that both viral proteins can induce cell death by an apoptotic mechanism via caspases. HBX appears to trigger more cell death than HBE, while HBE-induced an initial proliferation of the cell culture followed by cell death. HBX-induced apoptosis appears to involve both extrinsic and intrinsic cell death systems through the Fas system and the mitochondria, respectively. There is also a total loss of the PI3K/Akt pathway surivial signals. The HBE-induced apoptosis appears to be through DNA damage triggering an intrinsic cell death program, coupled with a partial loss of the PI3K/Akt pathway that allows GSK313 to be activated, while keeping FHKR inactive. In both cases, the viral cell death can be prevented using the correct dosage of IL-6 stimulation, while loss of serum or the addition of ethanol can have an overall positive effect on the viability of HBX and HBE transfected cells. The deaths can also be prevented in varing degress by the inhibition of MEKI and PPIA/2A suggesting these pathways are involved probably by cross talking.